FUT8: AN EMERGING DRIVER OF METASTASIS - Zil-; Hussain Shah (ziauddin University, 2024)
This critical research periodical is mainly based on critical review of research article titled "A Systems Biology Approach Identifies FUT8 as a Driver of Melanoma Metastasis" published in Cancer Cell by Agrawal et al1. Glycosylation is the distinct cell and microenvironment relatedmechanism establishing glycosidic linkages with major nutrients by the action of various enzymes. Meezan et al. described aberrant glycosylation in cancer in 1969 and since then it has been recognized that process of glycosylation is altered during cancer cell transformation and its progression2. The above mentioned research article is also part of continuation of this concept in which Agrawal et al. documented the role of glycosyl transferase FUT8 as a facilitator of metastasis in melanoma. This facilitation opens new avenues for scientists to develop novel therapies making core fucosylation as a target for metastatic tumors.